The advantage of using Nordic Walking in the rehabilitation of persons with PD-evidence based review - Żyżniewska-Banaszak, Ewelina; Woitas-Ślubowska, Donata; Żyżniewski, Kuba; Gębka, Magdalena (Akademia Wychowania Fizycznego w Poznaniu)
Parkinson’s disease (PD) is a chronic, progressive disease of the central nervous system, which gradually impairs functioning of the people who suffer from it. It is the second most prevalent neurodegenerative disease after the Alzheimer’s disease. PD affects both women and men. The risk of PD increases with age. Patients diagnosed with PD present with progressive difficulty in walking, speaking and in the ability to perform activities of daily living (ADL). The symptoms of PD include resting tremor of the upper limbs, postural instability and walking difficulty. Comprehensive rehabilitation is recommended inpatients with PD. It improves muscle strength, the sense of balance, mobility and independence. One form of the rehabilitation is Nordic Walking training recommended by the clinician based on the initial functional assessment where indications and contraindications for exercises are established. This paper presents evidence based recommendations for classes of Nordic Walking in the rehabilitation of people with PD
Keywords: Parkinson’s disease; rehabilitation; Nordic Walking; LVST-BIG